Pengaruh Gaya Kepemimpinan Transformasional Dan Disiplin Kerja Terhadap Kinerja Karyawan Pt Sinar Mandiri Teknik Bekasi - Baidowi, Ahmad; Wanta, Wanta; Hidayaty, Dwi Epty (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
Employee performance is one of the most important things in the company, employee performance at PT Sinar Mandiri Teknik Bekasi is required to achieve predetermined company targets. However, in reality in the last two years the targets that have been planned or set are still not achieved as expected. The purpose of this study was to determine and analyze the effect of transformational leadership style, work discipline partially and simultaneously on the performance of employees of PT Sinar Mandiri Teknik Bekasi. The method used in this research is quantitative descriptive verification. The population in this study were all 103 employees of PT Sinar Mandiri Teknik Bekasi with a sample calculation using the Slovin formula and a sample size of 51 employees was obtained. Data collection using a questionnaire, and data analysis techniques using multiple linear regression analysis with the help of analytical tools, namely SPSS version 26. The results of the research conducted there is a significant positive partial effect of transformational leadership style on performance, there is a significant positive partial effect of work discipline on performance, and there is a simultaneous effect of transformational leadership style and significant positive work discipline on performance. The more the transformational leadership style develops and maintains work discipline, the more employee performance will increase. Leaders who have a transformational leadership style can increase employee motivation and dedication, encourage them to work with passion and strive to achieve maximum performance in their work. Work discipline that has been implemented in the company should be maintained in order to improve performance by achieving targets on time. transformational leadership style and work discipline have an important role in improving employee performance.